Response of Advanced Rice Lines from Inter and Intraspecific Backgrounds to Saline Stress Conditions - Cobos, Fernando; Reyes, Walter; Perez-Almeida, Iris; Medina, Reina; Garcia, Pedro; Alvarez, Rosa (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
The growth and development of rice crops can be adversely affected by several stresses, including salinity. This study aimed to determine the performance of rice genotypes composed of advanced lines from interspecific and intraspecific crosses between Oryza sativa L. ssp. japonica x O. rufipogon G, grown in saline conditions achieved by NaCl applications in the irrigation water (electrical conductivity (EC) of 7.0 and 0.2 dS/m) in a greenhouse. A randomized complete block design with six replications was used with a split-plot arrangement. Grain yield, root length, number of panicles, root, and shoot dry biomass were evaluated. The genotypes showed wide phenotypic variability in the response to salt stress in all the variables studied, except for shoot dry biomass. The advanced lines from interspecific crosses showed a greater number of genotypes with tolerance to salt stress and exhibited a greater number of transgressive lines in group 1, compared to the lines of group 2, japonica x japonica. The lines that resulted in greater tolerance to salt stress can be used in genetic improvement programs that seek to develop rice cultivars tolerant to saline stress.